STRATEGI KOMUNIKASI KEMENTERIAN AGAMA KOTA PEKANBARU DALAM MENGIMPLEMENTASIKAN PROGRAM BANTUAN SISWA MISKIN (BSM) (Strategi Komunikasi Onong Uchjana Effendy) - Reza Restanto Pahlawan; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research, entitled the Communication Strategy Ministry of Religion of the Implementation of BSM Program. The purpose of this research was to determine the Communication Strategy Ministry of Religion of the Implementation of BSM program.This research used a qualitative approach with descriptive methods. Data collection techniques used were observation, interview, and documentation study, by researchers as a key instrument. The sending technique in this research using purposive sampling that researches pointed directly informant who was supposed to provide accurate information. Test the validity of data is done with reliability testing and validity testing. Descriptive analysis of the result obtained by triangulation strategy fulfillment of the communication strategy outline namely: 1) strategy of communicator selection and planning; 2) messaging strategy; 3) strategy of communication media selection; and 4) Strategy of communicator selection and planning.The results of this research indicate that communication strategy of ministry of religion of the implementation of BSM Program has been already on target. It can be seen from fulfillment component of communication strategy as follows 1) has been choosen a communicator who has educational background in accordance with his job, has a credibility, and has an attractiveness; 2) composed messages using verbal messages that is face to face, monitoring, a letter, and internet access, and nonverbal messages that is body gesture and face expression, using the explanatory message of serving method; 3) has been choosen using a mix of direct media that is face to face, by phone, and by a letter, and indirect media that is the internet media and 4) has been choosen communican in according to the technical guidelines PIP 2016 and determining criteria according to KMA No 258 2015, and has a special reference in determining acceptance criteria of BSM programKeyword: Communication Strategy, BSM Program, Component of Sommunication Strategy.